2021
DOI: 10.1177/08997640211057438
|View full text |Cite
|
Sign up to set email alerts
|

Examining Chinese Charitable Giving Under State Intervention: A Political Participation Perspective

Abstract: While it is prominent for governments across the globe to promote charitable giving, few governments directly intervene in charitable fundraising due to ethical and political risks. An exception is the Chinese government that has actively sought private donations. Using a national dataset of Chinese giving, this study explores from a general political participation perspective how individuals responded to different levels of state intervention in private charity. It finds that people made (a) voluntary donatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Those cases are prevalent rather than sporadic (L. Feng & Zhang, 2014). 3 Drawing data from the 2012 Chinese General Social Survey, Hu and Kong (2021) found that in comparison with people working in the private sector, employees salaried by the state and state-owned enterprises were more likely to donate when the donation was either suggested or coerced by government and less likely to donate when the donation was voluntary.…”
Section: Political Connectionsmentioning
confidence: 99%
“…Those cases are prevalent rather than sporadic (L. Feng & Zhang, 2014). 3 Drawing data from the 2012 Chinese General Social Survey, Hu and Kong (2021) found that in comparison with people working in the private sector, employees salaried by the state and state-owned enterprises were more likely to donate when the donation was either suggested or coerced by government and less likely to donate when the donation was voluntary.…”
Section: Political Connectionsmentioning
confidence: 99%